Forty Years of American Sentencing Guidelines: what Have We Learned? - Frase, Richard S. (Crime and justice, 2019)
Since 1980, 22 state and federal jurisdictions have adopted sentencing guidelines. Nineteen still have them. No two systems are alike. Experience suggests that any well-designed system requires five core features: a permanent, balanced, independent, and adequately funded sentencing commission; typical-case presumptive sentences and departure criteria; a hybrid sentencing theory that recognizes both retributive and crime control purposes; balance between the competing benefits of rules and discretion; and sentence recommendations informed by resource and demographic impact assessments. Balance is needed in terms of commission composition, between conflicting sentencing purposes, between rules and discretion, and between the influence of the commission, the legislature, and case-level actors. Guidelines proponents disagree about a number of important issues. Some relate to which crimes and sentencing issues should be regulated. Others concern the design details that determine how the system actually works. It is clear, however, that preguidelines regimes of unstructured, highly discretionary sentencing are unacceptable and that commission-drafted guidelines, endorsed by the American Bar Association and the American Law Institute, are the only successful sentencing reform model. In four decades, no competing model of comparable detail and scope has been seriously proposed.